Both modular and single‐domain Type I polyketide synthases are expressed in the brevetoxin‐producing dinoflagellate, Karenia brevis (Dinophyceae). Issue 6 (3rd November 2017) - Van Dolah, Frances M.; Kohli, Gurjeet S.; Morey, Jeanine S.; Murray, Shauna A.
Abstract : Dinoflagellates are prolific producers of polyketide compounds, many of which are potent toxins with adverse impacts on human and marine animal health. To identify polyketide synthase (PKS) genes in the brevetoxin‐producing dinoflagellate, Karenia brevis, we assembled a transcriptome from 595 million Illumina reads, sampled under different growth conditions. The assembly included 125, 687 transcripts greater than 300 nt in length, with over half having >100× coverage. We found 121 transcripts encoding Type I ketosynthase (KS) domains, of which 99 encoded single KS domains, while 22 contained multiple KS domains arranged in 1–3 protein modules. Phylogenetic analysis placed all single domain and a majority of multidomain KSs within a monophyletic clade of protist PKSs. In contrast with the highly amplified single‐domain KSs, only eight single‐domain ketoreductase transcripts were found in the assembly, suggesting that they are more evolutionarily conserved. The multidomain PKSs were dominated by trans ‐acyltransferase architectures, which were recently shown to be prevalent in other algal protists. Karenia brevis also expressed several hybrid nonribosomal peptide synthetase (NRPS)/PKS sequences, including a burA ‐like sequence previously reported in a wide variety of dinoflagellates. This contrasts with a similarly deep transcriptome of Gambierdiscus polynesiensis, which lacked NRPS/PKS other than the burA ‐like transcript, and may reflect the presence of amide‐containing polyketides in K. brevis and their absence from G. polynesiensis . In concert with other recent transcriptome analyses, this study provides evidence for both single domain and multidomain PKSs in the synthesis of polyketide compounds in dinoflagellates.